Complete genome sequence of Jiangella gansuensis strain YIM 002T (DSM 44835T), the type species of the genus Jiangella and source of new antibiotic compounds. Issue 1 (December 2017) - Jiao, Jian-Yu; Carro, Lorena; Liu, Lan; Gao, Xiao-Yang; Zhang, Xiao-Tong; Hozzein, Wael; Lapidus, Alla; Huntemann, Marcel; Reddy, T.; Varghese, Neha; Hadjithomas, Michalis; Ivanova, Natalia; et al.
Abstract Jiangella gansuensis strain YIM 002T is the type strain of the type species of the genusJiangella, which is at the present time composed of five species, and was isolated from desert soil sample in Gansu Province (China). The five strains of this genus are clustered in a monophyletic group when closer actinobacterial genera are used to infer a 16S rRNA gene sequence phylogeny. The study of this genome is part of theG enomic E ncyclopedia of B acteria and A rchaea project, and here we describe the complete genome sequence and annotation of this taxon. The genome ofJ. gansuensis strain YIM 002T contains a single scaffold of size 5, 585, 780 bp, which involves 149 pseudogenes, 4905 protein-coding genes and 50 RNA genes, including 2520 hypothetical proteins and 4 rRNA genes. From the investigation of genome sizes ofJiangella species, J. gansuensis shows a smaller size, which indicates this strain might have discarded too much genetic information to adapt to desert environment. Seven new compounds from this bacterium have recently been described; however, its potential should be higher, as secondary metabolite gene cluster analysis predicted 60 gene clusters, including the potential to produce the pristinamycin.